Strength analysis of Diliman silt stabilized by Mount Pinatubo ejecta and lime - Ansuas, Angelo Baye B.; Reyes, Katrina R.
Pyroclastic material ejected from the eruption of Mount Pinatubo in 1991, specifically volcanic ash (VA), is proposed to be a potential material for stabilization of soils, particularly Diliman Silt. Volcanic ash samples and soil samples are characterized using X-ray fluorescence and various geotechnical tests respectively. Varying concentrations of volcanic ash, lime, and water is observed for the production of soil mixture samples which would all undergo the Unconfined Compression Test (UCT). Results from the test were obtained to determine the effect of the proposed material to the soil and were used to conduct statistical analysis as well as cost analysis. Optimum mixtures were also identified from the results based on the categories of strength and cost efficiency.